ENTROPIC EVALUATION OF INNOVATIVE SYSTEMS ENTERPRISE DEVELOPMENT - TKACHENKO, IVAN; SHARKO, VITALII; ZAVHORODNIA, TATIANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The model of the production complex always includes the object of management and the subject of management in the form of appropriate systems. The method of realization of relations between them depends on the level of development of industrial relations. At the present stage of development of machinery and technology to the method of implementation of these relations requires their integration into a single corporate governance system.In recent years, several approaches have been used to identify the mechanisms underlying the development and operation of complex systems. Particularly useful results were obtained in their study by methods of random matrix theory, mono- and multifractal analysis, chaos theory with reconstruction of the system trajectory in phase space and determination of its parameters such as correlation dimension, spectrum of Lyapunov indicators, recurrent maps. However, the use of some of the methods requires the stationary nature of the studied data, requires long time series and a comprehensive calculation of several parameters. Another approach to considering the features of complex systems is to calculate the characteristics of entropy.The paper considers problematic issues related to the innovative development of machine-building enterprises. An algorithm for increasing the innovation potential of an industrial enterprise is proposed. The authors present a variant of assessing the systemic nature of innovative development of machine-building enterprises. The indicators of evaluation and increase of the level of innovative development of industrial enterprises are systematized. The integral index and the system entropy index are determined.
Keywords: enterprise; mechanical engineering; entropy; innovative development; integrated indicator